Yesus Kristus Sang Gembala Penyembuh: Kristologi dalam Konteks Safeguarding terhadap Anak - Antonius Bagas Prasetya Adi Nugraha (Sekolah Tinggi Filsafat Seminari Pineleng, 2023)
This article aims to inspire readers' perspectives and help the Indonesian Catholic Church act appropriately and wisely when facing cases of sexual violence and abuse. The method used in this article is Theology in Creation, which is used to deepen the understanding of Christ as a healing shepherd who cares and fights for justice. The systematics of this article begins with the introduction of the problem, followed by a discussion of cases of sexual abuse that occurred in the history of the Catholic Church. Then, the article discusses power in Michel Foucault's theory and its challenges for political sociology. Next, the article highlights the importance of building a safe culture within the Church and protecting children from abuse. The novelty of this article lies in the Theology in Creation approach used to deepen the understanding of Christ as the healing shepherd. The article also invites the Indonesian Catholic Church to become more concerned and responsive to cases of sexual violence and abuse and to implement effective protection protocols.